PIK3CA vascular overgrowth syndromes: an update. Issue 4 (August 2020) - Hughes, Meagan; Hao, Michelle; Luu, Minnelly
Abstract : Purpose of review: Over the past decade many previously poorly understood vascular malformation disorders have been linked to somatic activating mutations in PIK3CA, which regulates cell survival and growth via activation of the mTOR1-AKT pathway. The goal of this article is to describe and provide an update on the clinical features, complications, and management strategies for the PIK3CA-related overgrowth spectrum (PROS). Recent findings: PROS encompasses a heterogenous group of disorders with complications related to the tissues harboring the mutation. Vascular malformation syndromes, such as Klippel–Trenaunay syndrome and Congenital Lipomatous Overgrowth Vascular malformations Epidermal nevi and Skeletal abnormalities, have an increased risk of thromboembolic complications, which is accentuated postprocedurally. Asymmetric overgrowth, particularly of limbs, results in a high rate of orthopedic complications. Hypoglycemia screening in the neonatal period and ongoing monitoring for growth failure is recommended in megalencephaly capillary malformation due to its association with multiple endocrinopathies. Recently, sirolimus, an mTOR1 inhibitor, has shown promise in vascular anomalies and now PROS. PIK3CA direct inhibitor, Alpelisib (BYL719), was recently trialed with significant clinical benefit. Summary: As the pathogenesis of these conditions is better elucidated and targeted treatments are developed, recognizing the clinical features, comorbidities, and evolving therapeutic landscape across the PROS spectrum becomes more crucial for optimization of care.